Exchange listing changes: volatility and liquidity effects in Taiwan - P. Blenman, Lloyd; Chen, Dar-Hsin; Duan, Chang-wen (Universiti Utara Malaysia, 2003)
We examine the volatility, liquidity and returns effects on stocks that switch exchange listings from the ROSE to the TSE in Taiwan from 1992 to 2000. Switching Jims earn statistically positive returns before the transfer day and earn statistically negative returns after that day. We find evidence of improved liquidity, ownership dispersion and actual trading volume for such firms. The relative volatility of trading volume, compared against the firms ' own histories, and volatility of return also increase after a listing change. We show that increased trading volume and liquidity are associated with the abnormal returns around the transfer date. We find no evidence that the past earnings of firms significantly affect the abnormal returns realized in the post-listing period.